Specialization Courses in the French (Education and Literature) Study Program in Indonesia and the Challenges of the Post-Pandemic World of Work - Setia RINI; Diana ROSITA; Indah Nevira TRISNA (Department of French Language Education, Universitas Pendidikan Indonesia, 2024)
Job opportunities for graduates of the French Language Program are currently increasingly promising. But of course, graduates must have good and even superior competencies in order to compete with graduates in the same field from various universities in Indonesia. Therefore, the existence of Specialization Courses is a very good step to equip graduates with qualified competencies, especially in the field of French. Specialized Courts can help graduates to be able to compete with a wider range of occupations. Opportunities for graduates to get jobs will be increasingly wide open. Descriptive qualitative method will be used in the observation and data processing and the presentation of the results later. In addition, in the long term, of course, this mapping will be very useful, considering that there are quite a lot of French (education literature) courses in Indonesia, especially in several well-known universities. Especially in the global era, the era of the industrial revolution 4.0 or 5.0, the disruptive era and also the current existence of MBKM which forces all levels of education and the world of work to be able to adapt and change very quickly.